New drugs in early development for treating multiple myeloma: all that glitters is not gold. (1st September 2020) - Bertamini, Luca; Bonello, Francesca; Boccadoro, Mario; Bringhen, Sara
ABSTRACT: Introduction: The last twenty years have introduced new therapeutic agents for multiple myeloma (MM); these include proteasome inhibitors (PIs), immunomodulatory drugs (IMDs) and monoclonal antibodies (mAbs). However, MM remains incurable, hence there is an unmet need for new agents for the treatment of advanced refractory disease. New agents could also be used in early lines to achieve improved, more sustained remission. Areas covered: We review the most promising agents investigated in early-phase trials for the treatment of MM and provide an emphasis on new agents directed against well-known targets (new PIs, IMDs and anti-CD38 mAbs). Drugs that work through distinct and numerous mechanisms of action (e.g. pro-apoptotic agents and tyrosine kinase inhibitors) and innovative immunotherapeutic approaches are also described. The paper culminates with our perspective on therapeutic approaches on the horizon for this disease. Expert opinion: IMD iberdomide and the export protein inhibitor selinexor demonstrated efficacy in heavily pretreated patients who had no other therapeutic options. We expect that immunotherapy with anti-BCMA BTEs and ADCs will revolutionize the approach to treating the early stages of the disease. Data on venetoclax in t(11;14)-positive patients may pave the way for personalized therapy. Not all new agents under early clinical evaluation will be investigated in regulatory phase III trials; one of the most important challenges is to identify those that could make a difference.